Pengaruh Literasi Keuangan Digital dan Konformitas Terhadap Perilaku Konsumtif Mahasiswa Universitas Negeri Padang - Nisa Umami; Rita Syofyan (Jurnal Salingka Nagari, 2023)
This study aims to determine and analyze 1) the effect of digital financial literacy on the consumptive behavior of students of Padang State University, 2) the effect of conformity on the consumptive behavior of students of Padang State University, and 3) the effect of digital financial literacy and conformity on the consumptive behavior of students of Padang State University. This is a descriptive and assosiative research. The sampling technique used is purposive sampling, with 381 sampels. The analysis method used is multiple linear regression analysis using SPSS 22. Based on the results of the study, it is known that variables that partially affect consumptive behavior are digital financial literacy with a significance value of 0.000<0.05, conformity variable has effect on consumptive behavior with a significance value of 0.012<0.05. Meanwhile, for simultaneous testing of variables of digital financial literacy and conformity affect consumptive behavior with a significance value of 0.000<0.05. The magnitude of the influence of the influence of the independent variable on the dependent variable is 8,4%.